Insights into evaluating the toxic effects of nitrofurazone on ecological integrity in marine ecosystems using periphytic ciliate communities - Syed Shabi Ul Hassan Kazmi; Uroosa; Alan Warren; Henglong Xu (Ecological Indicators, 2022)
Despite its detrimental effects on ecosystems, the broad-spectrum antibiotic nitrofurazone is extensively used in the aquaculture industry worldwide. However, the impacts of nitrofurazone toxicity on ecological integrity are still unclear. In this study, a community-based bioassay was used to evaluate the toxicity of nitrofurazone to periphytic ciliates in a concentration gradient using five treatments (0, 1, 2, 4 and 8 mg l−1). The periphytic ciliate communities were collected from coastal waters of the Yellow Sea near the mouth of Jiaozhou Bay at Qingdao, in northern China. After exposure to nitrofurazone, these communities showed toxicity dynamics like high variability in species composition. Species richness and total abundance decreased in a dose-dependent manner, with total abundance dropping sharply at the 8 mg l−1 concentration of nitrofurazone. Multivariate analyses demonstrated variations in the patterns of community structure driven by nitrofurazone toxicity, and these patterns differed significantly depending on the nitrofurazone concentration (P < 0.05). The findings of this study suggest that periphytic ciliate communities can potentially be used in bioassays for assessing nitrofurazone toxicity in marine ecosystems.